Impaired oligodendrogenesis and myelination by elevated S100B levels during neurodevelopment. (February 2018) - Santos, Gisela; Barateiro, Andreia; Gomes, Cláudio M.; Brites, Dora; Fernandes, Adelaide
Abstract: High levels of the inflammatory molecule S100B protein have been identified in sera from several perinatal inflammatory conditions involving myelin damage and associated with an adverse prognosis or the emergence of sequelea . S100B is essential for oligodendrocyte (OL) differentiation and maturation, but it remains to be established if excessive levels of released S100B upon early brain injury are deleterious in the neurodevelopmental period. Here, we investigated this possibility by evaluating how elevated S100B affects oligodendrogenesis during this period. First, using primary cultures of OL we observed that damage-induced micromolar levels of S100B impair OL differentiation process. S100B elevated concentrations reduced both transition from immature NG2 + oligodendrocyte precursor cells (OPC) to mature MBP +  OL, and morphological maturation of differentiated OL. Interestingly, these effects were abolished by the use of receptor for advanced glycation end-products (RAGE) antagonist FPS-ZM1, suggesting an involvement of the S100B-RAGE axis on oligodendrogenesis impairment. Next, we used organotypic cerebellar slice cultures to explore the role of S100B in a more complex multicellular environment. Also in this model excessive S100B levels impaired oligodendrogenesis resulting in a reduced myelination. Further, elevated S100B levels compromised neuronal and synaptic integrity, while inducing astrogliosis, nuclear factor (NF)-kB activation and inflammation. Again, the FPS-ZM1 co-treatment prevented S100B-induced damaging effects. Overall, our results indicate that persistently elevated S100B levels have deleterious effects during the neurodevelopmental period through RAGE-dependent processes. Thus, targeting high S100B levels and/or S100B-RAGE interaction may constitute good therapeutic strategies to reduce brain injury, including deficits in neuronal architecture, synaptogenesis and myelination associated with perinatal inflammatory conditions. Highlights: Elevated S100B levels impair oligodendrogenesis in primary rat oligodendrocytes. Elevated S100B levels impair myelination in organotypic cerebellar slices. Neuronal maturation is reduced by elevated S100B in organotypic cerebellar slices. Elevated S100B induce an inflammatory response in organotypic cerebellar slices. S100B effects are mediated by RAGE and outcompeted by the specific RAGE antagonist.